Aplicação de eletrocoagulação no tratamento de efluentes de abatedouro de aves utilizando eletrodos de ferro e alumínio para remoção de nutrientes - Potrich, Mateus Cescon (2019)
Brazil is one of the largest chicken meat producers and exporters in the world and this industry wastewater has a high pollutantload, mainly organic matter and nutrients content, which dischargecan cause eutrophication in the receiving water bodies. Electrocoagulation has been studied to remove different pollutants fromdifferent sources, therefore, this workobjective wasto evaluate the electrocoagulation process in a poultry slaughterhouse wastewater treatmentusing iron and aluminum electrodes to remove nutrients. After wastewater characterization, a Central Composite Rotatable Design 2³, was applied to evaluate the independent variables influence as current density, initial pH and time on the response variables as total nitrogen and phosphorus removal. In the best condition found for nutrients removal, the other physical-chemical, microbiological and ecotoxicological parameters removalwas also investigated and the treatment costwas evaluated to determinewhich electrode material, iron or aluminum, was most efficient. In the rawwastewater, selected the best condition was current density 20 mA cm-2, original wastewater pH6.2, and a time of 20 min, the nitrogen and phosphorus removal resultswere similar for both electrodes material. Iron electrode treatment showed better COD, oils and greases, solids and ecotoxicity removal, besides being cheaper (R $ 16.52 m-3). In the polished wastewater, the treatment with aluminum electrode was more efficient under the conditions current density 30 mA cm-2, originalpH8 and time 10 min and obtained the lowest cost R $ 15.56 m-3. The iron electrode treatment added color, turbidity andsolids to the polished wastewater, due to the light flakes formation, separation difficultyand iron ions oxidation. Both electrodes reduced the ecotoxicity in the polished wastewater. The treatments were ineffective for ammonianitrogen and microbiological parameters reduction, besides increased the final pH in both wastewater. In the iron electrode treatment case, the final pH exceeds the limits established bylegislation, requiring correction for release into water bodies. The results show that the iron and aluminum electrodes are efficient in nutrients and other pollutants removal, andthe electrocoagulation being a viable treatment for poultry slaughterhouseswastewater.